Rhodium‐Catalyzed Cascade Reactions of Indoles with 4‐Hydroxy‐2‐Alkynoates for the Synthesis of Indole‐Fused Polyheterocycles. Issue 14 (21st June 2020) - Wu, Xiaowei; Li, Pinyi; Lu, Yangbin; Qiao, Jin; Zhao, Jingwei; Jia, Xiuwen; Ni, Hangcheng; Kong, Lichun; Zhang, Xiaoning; Zhao, Fei
Abstract: Herein, an efficient and regioselective Rh(III)‐catalyzed [4+2] annulation/lactonization cascade of indoles with 4‐hydroxy‐2‐alkynoates at room temperature to access the furo[3′, 4′:4, 5]pyrimido[1, 6‐ a ]indole‐1, 5(3 H, 4 H )‐diones is described. This method features mild reaction conditions, operational simplicity, excellent regioselectivity, broad substrate scope with good functional group tolerance, and good to excellent yields. Abstract :